P101 Peripheral blood type 2 innate lymphoid cell count in patients with severe eosinophilic asthma. (12th November 2015) - Hilvering, B; Go, S; Stoeger, L; Borg, K; Connelly, C; Thulborn, S; Pahlke, S; Pavord, ID; Xue, L
Abstract : Background: A subgroup of patients with severe asthma have persistent eosinophilic airway inflammation despite treatment with high intensity corticosteroid treatment. One possible explanation for this pattern of disease is involvement of a type 2 innate lymphoid cells (ILC2s) dependant and relatively corticosteroid resistant pathway generating type 2 cytokines such as IL-5 and Il-13. The presence of high numbers of ILC2s in the nasal polyps commonly associated with severe eosinophilic asthma supports this view. We have carried out a cross-sectional study testing the hypothesis that ILC2 counts are increased in peripheral blood of patients with severe eosinophilic asthma. Methods: Blood was taken from 9 controls and 33 patients with asthma, 23 of whom met the 2014 ERS/ATS guideline criteria for severe asthma and had historical evidence of eosinophilic airway inflammation as defined before (Pavord et al . Lancet 2012;380:651–9). ILC2 were measured as lineage- CD45 + CD127 + CRTH2+ by flow cytometry and numbers presented as total cell counts and% peripheral blood mononuclear cells. Results: ILC2 c ounts were repeatable within patients (ICC 0.97; n = 6). Mean ± SD ILC2 counts were 566 ± 379, 323 ± 224, 437 ± 628 and 429 ± 421cells/mL (Figure 1A ) and 0.034 ± 0.022, 0.02 ± 0.017, 0.020 ± 0.028 and 0.019 ± 0.014% of total lymphocytes (Figure 1B ) in normal controls (n = 9), patients with mild to moderate asthma (n = 10), patients with severe asthma at BTS step 4 (n = 12), and patients with severe asthma at BTS step 5 (n = 11) respectively. Conclusion: Type 2 innate lymphoid cells are scarce in peripheral blood but can be measured consistently. We found no evidence of increased counts in peripheral blood from patients with severe eosinophilic asthma.